Layout of the Medical Record Unit of Dr. Hospital. H. Moch Ansari Saleh Banjarmasin - Husin Husin; Galih Persadha; Firda Aurelia Nurhaliza (Politeknik Unggulan Kalimantan, 2021)
Spatial planning is the arrangement of tools in the right location and workplace arrangements that create satisfaction for employees. The arrangement of the workspace in the medical record unit affects the service activities provided to patients, so that the workspace arrangement in the medical record unit needs to be considered so that the services provided by the medical record unit can run smoothly. Based on a preliminary study at RSUD dr. H. Moch Ansari Saleh through observation, researchers found the fact that the medical record management room was narrow, this made the officers jostling and when they passed each other they had to take turns, and the placement of facilities or facilities that were less needed made the room narrower. . And the results of interviews with medical records officers that he said officers work by walking back and forth from one table to another at a distance apart because the layout does not match the medical record workflow, this has an impact on the smoothness of service and reduces work speed. The purpose of this study Describes the layout of the medical record work unit at RSUD dr.H.Moch Ansari Saleh. This type of research method used is descriptive qualitative. Methods of data collection using interviews and observation. Based on the results of the research, the medical record unit room was not neatly arranged, the work desk was not in accordance with the medical record data processing flow, there were several work desks between officers who did not have distance, and for the filing room the layout was appropriate and did not hinder access. The area of ​​​​the medical record work unit is narrow, it is necessary to expand the room which has an impact on the comfort of the officer in working and for the filing room, it is sufficient in terms of the area of ​​​​the room. The facilities in data processing are still not suitable, it is necessary to add a work desk because there are officers who do not have a work desk